Temparature stability of loop-mediated isothermal amplification (LAMP) reagetns for the rapid detection of monodon baculovirus (MBV). - Pama, Jennifer Anne S.
Monodon baculovirus (MBV) is one of the important shrimp pathogen infecting both wild and cultured shrimp populations of Penaeusmonodon in the Philippines (Caipang et al.' 2011a). One of the molecular techniques used for pathogen detection is Loop-mediated Isothermal Amplification (LAMP). It employs a set of four to six specifically designed primers used to target eight distinct sequences of a target gene (Parida et al.' 2008). LAMP relies on the strand displacement activity of a DNA polymerase for separation of dsDNA strands and proceeds at isothermal conditions (Notomi et al., 2000). The study aims to assess the efficiency of LAMP in the rapid detection of the Philippine isolates of MBV in shrimp, Paeusmonodon when LAMP reagents are stored at 20 - degrees centigrade (recommended storage temperature) and 27 degrees centigrade (Philippine room centigrade). DNA extraction and primer designs were followed from the study of Caipang et al (2011). LAMP reagents were preformulated and stored at different temperatures for 35 days. Reactions were conducted every five days by means of LAMP assay. LAMP reaction products were performed on a 2.0 percent agarose gel that are stained with ethidium bromide and viewed under gel documentation system . Results of the study showed that treatments stored at - 20 degrees centigrade is the ideal storage temperature for LAMP reagents, followed by treatments stored at 27 degrees centigrade (15 days of storage). Treatments with reagents, primers, DNA templates and Bst DNA polymerase stored at separate temperatures were least stable. Thus, LAMP in a single tube with preformulated reaction mixes consisting of primers, reagents and DNA template, suggest that reagents can be prepared in advance in large batches and stored in temperatures - 20 degrees centigrade and 27 degrees centigrade until next LAMP assay.